Kajian History Tardisi Pencak Silat Pelintau Sebagai Sumber Belajar Sejarah Lokal - Okhaifi Prasetyo; Muhammad Al Dilwan; Dimas Ade Gunawan (PT. Hasba Edukasi Mandiri, 2025)
The history of the Pelintau Pencak Silat tradition is not widely known by the young generation, especially school students. This research aims to explore the history and development of Pencak Silat Pelintau and its relevance as a source of learning local history. This research uses historical methods with a qualitative approach: research steps, namely heuristics, verification, interpretation, and historiography. The research results show that Pencak Silat Pelintau is an integral part of the history and culture of the Tamiang people, which not only functions as a martial art but also reflects strong historical values. As a cultural heritage recognized as Indonesia’s Intangible Cultural Heritage (WBTB), this tradition is closely related to the Tamiang people’s struggle against colonialism. Therefore, its use in learning local history becomes relevant in helping students understand the nation's history through a regional cultural perspective. The integration of Pencak Silat Pelintau in the curriculum can be done by preparing teaching modules based on local culture and applying experience-based learning methods, such as direct observation, interviews with cultural actors, and analysis of historical documents. With an innovative and contextual approach, Pencak Silat Pelintau can be an effective, engaging and meaningful learning medium for the younger generation to understand the history, culture and heroic values ​​inherited from their ancestors.